EVOLUTIONARY IMPLICATIONS OF SELF-COMPATIBILITY AND REPRODUCTIVE FITNESS IN THE APOMICTIC RANUNCULUS AURICOMUS POLYPLOID COMPLEX (RANUNCULACEAE) - Hörandl, Elvira (2008)
Uniparental reproduction has often been regarded as advantageous for colonization. In pseudogamous a pomicts, reproduction via single individuals requires self-pollination and consequently self-compatibility (SC) for production of viable seeds. SC and reproductive fitness have been studied in diploid and polyploid taxa of the Ranunculus auricomus complex via pollinator exclusion tests, assessment of seed set, and germination rates. Reproductive fitness of sexuals exceeds that of apomicts and of F(1) hybrids but may fluctuate more strongly between years than is the case in apomicts. Diploid sexual taxa and also their F(1) hybrids are completely self-incompatible (SI). Auto-polyploid sexual cytotypes are also predominantly SI, which may have restricted their range expansion. The observed breakdown of SI in the rather widespread allohexaploid apomicts may be explained by initial partial SC inherited from semi-self-compatible ancestors and strong selection for SC genotypes. It is concluded that higher reproductive fitness of sexuals may help to maintain sexual populations when cross-pollination is available, whereas SC in apomicts may be advantageous in temporally and spatially unstable environments and also for colonization events. Results suggest that SC in connection with pseudogamous apomixis is an important factor for the observed distribution pattern of geographical parthenogenesis.